Understanding the Catholic Notion of Redemptive Suffering in a Contemporary Context - Yuen, Hiu-tung (Verbum Vitae, 2023)
Although the Catholic Church nowadays still officially values the ideas of self-sacrifice and the redemptive nature of suffering, academically, there exists a tendency to adapt these ideas to modern values. With the advancement of medical technology, the pursuit of health predominates the mindset of modern people and the practice of redemptive suffering turns out to be an outdated or even ridiculous idea. At the societal level, it is a problem concerning the incompatibility between Catholic dogmas and secular values. At the individual level, it is a question of believing these “empirically unbelievable” religious doctrines without being in a curious form of schizophrenia and insincerity. This paper attempts to examine the difficulties in understanding the Catholic notion of redemptive suffering in the twenty-first century. We attempt to demonstrate that the unintelligibility of this notion lies not in the idea of the willing sacrifice of a person for another human being; rather, it is more concerned with the content and way of suffering, as well as the explanation offered for it. We then suggest that taking the “supernatural Catholic worldview” seriously is an important condition to attain a deeper understanding of the notion of redemptive suffering. Lastly, we will examine whether the notion lacks contemporary significance by looking into some cases in the Catholic communities nowadays.